MeDict: Health Dictionary Application Using Damerau-Levenshtein Distance Algorithm - Wiwi Clarissa; Farica Perdana Putri (Universitas Multimedia Nusantara, 2020)
Typographical error often happens. It can occur due to mechanical errors or missed hands or fingers when typing. Someone's ignorance of how to spell correctly also can cause typographical errors. Dictionary application development has been carried out by various parties so that the searching process in the dictionary becomes more efficient. However, there is no word search optimization when the typographical error happens. Typographical errors in the searching process can result in the information sought cannot be found. The Damerau-Levenshtein Distance algorithm implemented to provide search suggestions when a typographical error occurs. This research aims to design and build a health dictionary application, MeDict, using the Damerau-Levenshtein Distance algorithm. Technology Acceptance Model (TAM) used to evaluate the application. The result is 86.2% stating strongly agree that the application can be useful and 86.9% stating strongly agree that the application can be used easily.